The Goals and Results of Auditing Investment Projects Financed by the EU - Bednarek, Piotr (Cele i rezultaty audytu projektów inwestycyjnych finansowanych z UE, 2010)
New legal regulations connected with increasing the corporate governance in public corporations in Poland as well as European Union law stipulating the conditions of using the funds allocated to infrastructure development indicate the need for greater control of investment projects. An essential part of this control is the project audit conducted by an independent party. The goals, range and results of these audits vary in practice, due to the differences in the guidelines provided by institutions managing the aid programs, different expectations of the project promoter and various levels of competence of the auditing team
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 9-14
Keywords: audit; project; European Union